KAJIAN YURIDIS TINDAK PIDANA PENGANIAYAAN YANG DILAKUKAN OLEH ANAK DENGAN MENGGUNAKAN PENDEKATAN RESTORATIVE JUSTICE (Studi Pada Putusan Pengadilan Negeri Karanganyar No. 01/Pid.Sus- Anak/2014/PN Krg dengan Putusan Pengadilan Negeri Banyumas No. 05/Pid.Sus-Anak/2015/PN Bms) - SANYOTO, S. DWI (Dinamika Hukum, 2017)
The purpose of this study are to: 1) Assess the approach to the concept ofrestorative justice in criminal child in Indonesia. 2) Assess considerationKaranganyar District Court in deciding the case the crime of persecution (brawl)done by children using restorative justice approach in Karanganyar District CourtNo. 01 / Pid.Sus Anak / 2014 / PN KRG with the District Court Banyumas No. 05 /Pid.Sus Anak / 2015 / PN Bms.Methods of approach in this paper is normative. Specifications of thisresearch using descriptive analysis. Source data using secondary data. Datacollection techniques using literature study and document research. To analyze thedata, researchers used a qualitative normative method.Based on the research results can be concluded that: 1) The concept of theapproach of restorative justice in the criminal assault of children is done with threealternatives, namely outside the legal system without the involvement of lawenforcement officials, outside the legal system to keep law enforcement officials, andas part of the system Justice. 2. a. Consideration of Karanganyar District Court indeciding the case the crime of persecution (brawl) done by children in KaranganyarDistrict Court No. 01 / Pid.Sus Anak / 2014 / PN KRG are in accordance with LawNo. 11 Year 2012 on Child Criminal Justice System. Judge considerations such factsin the trial and juridical facts, as well as seeing things that are burdensome andrelieve the defendant. The judge dropped imprisonment for 1 (one) year with thecriminal provisions need not be run unless the future Children convicted of acriminal offense again based on the decision of the judge, before a period of 1 (one)year and 6 (six) months gone and dropped anyway the child's criminal to undergo jobtraining for 3 (three) months. The judge also looked at the application of sanctions tothe child in prison is not appropriate because of psychological factors. b. BanyumasDistrict Court Judge consideration in deciding the case the crime of persecution(brawl) done by children on Decision No. 05 / Pid.Sus Anak /2015/ PN Bms include:(1) Severity of criminal or delinquency committed by children; (2) The state of thechild; (3) The state-parent households; (4) The relationship between the familymembers and the state of the environment; (5) Noting reports Supervisor Society andthe history of the defendant Child.Keywords: Crime Kids, Restorative Justice Approaches